Moralitas politik dalam pemilu 2004 dan implikasinya bagi Pendidikan Kewarganegaraan - Cholisin Cholisin (Jurnal Civics: Media Kajian Kewarganegaraan, 2004)
Morality in general election 2004, a long way off from expected. Various actions which dissolute political indication see clearly in course of and result of general election. Money politics, administrative collusion and crime by some of all legislative candidates, bureaucracy which not yet neutral politically, manipulation of voice enumeration, showing process of general election still not yet full respect the moral. General election also did not yet shown to yield all politician owning high binding (commitment) to respect the political morality. Its indication, general election not yet earned to yield the leader owning inner calm and trusted by people, general election tends to yield the politician principled weak politics party at ideology so that progressively strengthen to expand "political of corruption. " Not yet strength of political morality in general election 2004 represented factor which did not conducive for civic education, because real reference of citizen about how politicians have moral. This circumstance if let it can conducive to the belief crisis to existing political system. Therefore, study of civic education agreed with general election which require to be developed critically to form the rational and proportional attitude in general election. If this matter is done will be able to assist to overcome to expand belief crisis to general election and national of political system.